European Union conditionality as impetus for improved health systems in Croatia - Skopac, Jessica Spencer (ProQuest Dissertations & Theses, 2012)
Background: This dissertation explores how the "Europeanization" of Croatia has affected the Croatian health system and its stakeholders. Supranational organizations, such as the European Union, have the potential to harness the enthusiasm of candidate nations and to influence domestic policies of member states by imposing economic sanctions on countries that fail to comply with international health and human rights standards and by offering economic incentives to countries that do comply. Economic stability attendant to EU membership encourages nations to work together to overcome differences and to adopt social policy reforms by providing a tangible and imminent incentive. In this study, the researcher uses qualitative methodology to examine the evolution of Croatian health policy in the context of EU integration. Hypothesis: As a result of both active and passive leverage, the incentive of European Union (EU) membership has been the critical element responsible for health policy reforms in Croatia from 2003 to 2008. Methods: The methods employed in this descriptive case study are three-fold: historical process tracing, manifest content analysis of key documents in Croatian health policy and directed content analysis of stakeholder interviews. The content analysis included ten documents, consisting of legislation and strategic health policy reform initiatives. Sampling for the informant interviews was purposive and phenomenological. A total of thirty interview subjects were identified based upon authorship of documents discovered in the course of the literature review and through blanket emails to government ministries, NGOs, and other groups associated with health policy-making in Croatia. Based upon the 2001 Croatian Census Data, the sample was drawn from each of the four regions of Croatia: Dalmatia, Istria, Central Croatia, and Slavonia to represent a diverse sample based upon the following criteria: population size, geographic region of the country, ethnic diversity, and the severity of conflict/number of ethnic minorities present. The interview questionnaire consisted of ten questions designed to assess stakeholder experiences and attitudes about changes to the Croatian health system over the past decade. Results: Attitudes of stakeholders both shaped and reflected the priority areas and concerns that Croatian health policy reforms have sought to address. With respect to health policy priorities, and obstacles to achieving them, a general consensus exists between EU policy-makers, Croatian policy-makers, and the sample of stakeholders in the Croatian health system selected to participate in this dissertation research. Among the interview subjects, priorities fell into five broad categories: cost, efficiency, quality, access, and mentality. Three out of five of these priorities (Quality, Access, and Mentality) also appear in the health system policy agendas for Croatia and the EU. Document analysis revealed that none of the health policy reforms in Croatia were the result of active leverage during the formal harmonization negotiation process, but that the EU did have a strong influence on Croatian health policy in the form of passive leverage. However, the EU did apply active leverage in other economic and social policy areas and stakeholders believed that the effects of these reforms on social and economic conditions in Croatia have been largely positive. As a result, population health in Croatia may benefit from these economic and social policy changes as they affect social determinants of health. This phenomenon, latent active leverage, describes the indirect effects of active leverage on population health resulting from economic and social policy changes which were not specifically targeted health policy reforms. Conclusion: The incentive of EU membership has been the critical element responsible for health policy reforms in Croatia from 2003 to 2008, but primarily as a result of passive leverage. The EU has tremendous, and largely underutilized, potential to promote health system improvement by providing economic incentives to candidate countries as part of the integration process.